-(8n+4)=4n-2(6n+2)

Simple and best practice solution for -(8n+4)=4n-2(6n+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(8n+4)=4n-2(6n+2) equation:


Simplifying
-1(8n + 4) = 4n + -2(6n + 2)

Reorder the terms:
-1(4 + 8n) = 4n + -2(6n + 2)
(4 * -1 + 8n * -1) = 4n + -2(6n + 2)
(-4 + -8n) = 4n + -2(6n + 2)

Reorder the terms:
-4 + -8n = 4n + -2(2 + 6n)
-4 + -8n = 4n + (2 * -2 + 6n * -2)
-4 + -8n = 4n + (-4 + -12n)

Reorder the terms:
-4 + -8n = -4 + 4n + -12n

Combine like terms: 4n + -12n = -8n
-4 + -8n = -4 + -8n

Add '4' to each side of the equation.
-4 + 4 + -8n = -4 + 4 + -8n

Combine like terms: -4 + 4 = 0
0 + -8n = -4 + 4 + -8n
-8n = -4 + 4 + -8n

Combine like terms: -4 + 4 = 0
-8n = 0 + -8n
-8n = -8n

Add '8n' to each side of the equation.
-8n + 8n = -8n + 8n

Combine like terms: -8n + 8n = 0
0 = -8n + 8n

Combine like terms: -8n + 8n = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 5y=7xl | | 5-1m=13 | | -5(1-3x)+3x=-4x+5(5x+2) | | 62+(-5)= | | (31/-4)+(-5/8) | | 4x-4(1+3x)=-(1+5x) | | -5(-8X+2)=26+4X | | 8x+17=22 | | t-3t-7=4t-7 | | 5/6+c=1/3 | | 3(x-5)=7x | | 2x^3+x^2-37x-36=0 | | 5t+12=4-3t | | 3x(x+12)+2x(2x+4)=360 | | x^3+47x-35= | | 2(250-x)+x*4=600 | | -3/b=1 | | x^3+47x-35=0 | | -6=2m | | -3t+8= | | 2X-125=455 | | ((1+2x)/(4))(16) | | 14-4x=9x | | -6(2x-6)+9=-12x+45 | | 7x-9y=-20 | | m/-2=-20 | | f(x)=(x-8)(x+5)(x-2) | | 15+.5(.4)=25+.25(.4) | | 9x-5=9(x-7) | | -12=1y-21 | | 1/4a=1/2(3-a)+(a-4/4) | | 32r^2+8r+2=0 |

Equations solver categories